2016
DOI: 10.1021/acsnano.6b01402
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated Entry of Pristine Octahedral DNA Nanocages in Mammalian Cells

Abstract: DNA offers excellent programming properties for the generation of nanometer-scaled polyhedral structures with a broad variety of potential applications. Translation to biomedical applications requires improving stability in biological fluids, efficient and selective cell binding, and/or internalization of the assembled DNA nanostructures. Here, we report an investigation on the selective mechanism of cellular uptake of pristine DNA nanocages in cells expressing the receptor "oxidized low-density lipoprotein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 49 publications
5
70
0
1
Order By: Relevance
“…The authors showed that folate‐modified nanocages enter HeLa cells 40 times more than αFR‐negative A431 epidermal cancer cells, pointing to their specificity to αFR‐expressing cells after 24 h of incubation. In general, such specificity depends not only on the expression of αFR and but also on the expression of the receptor responsible for internalizing pristine nanocages, low‐density lipoprotein receptor (LOX‐1; see Section for the mechanistic details). Raniolo et al further compared the uptake of folate‐modified octahedral nanocages by HeLa cells, A431 cells, COS kidney fibroblasts, and COS cells that are engineered to overexpress LOX‐1 .…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors showed that folate‐modified nanocages enter HeLa cells 40 times more than αFR‐negative A431 epidermal cancer cells, pointing to their specificity to αFR‐expressing cells after 24 h of incubation. In general, such specificity depends not only on the expression of αFR and but also on the expression of the receptor responsible for internalizing pristine nanocages, low‐density lipoprotein receptor (LOX‐1; see Section for the mechanistic details). Raniolo et al further compared the uptake of folate‐modified octahedral nanocages by HeLa cells, A431 cells, COS kidney fibroblasts, and COS cells that are engineered to overexpress LOX‐1 .…”
Section: Governing Factors Of the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
“…By performing molecular simulations, the authors showed that the TDNs approach the cell membrane with their corners to minimize electrostatic repulsion. In 2016, Vindigni et al studied the mechanism for the cellular uptake of DNA octahedral nano‐cages of ≈11 nm in diameter . The authors transfected COS fibroblasts with DNA plasmids that encode LOX‐1 for generating LOX‐1‐expressing COS cells.…”
Section: Mechanisms For the Cellular Uptake Of Dna Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Receptor-mediated uptake of ab iotin-functionalised octahedral DNAc age has also been reported by Desideri, Biocca and co-workers. [147] This octahedral construct is taken up preferentially by the oxidised low density lipoprotein receptor-1 (LOX-1) which is atumour and cardiovascular disease marker.…”
Section: Drug Delivery Strategiesmentioning
confidence: 99%